(untitled) (Research, Society and Development, 2022)
The school institution is a privileged space for the construction of citizenship, therefore it must and can become an effective space for the exercise of democratic and solidary coexistence, aspects that will constitute the content of education itself in values. The objective of this work is to observe the education in values in the scope of the debates about the school curriculum and the valorization of life. Using a descriptive methodology, since a bibliographic review was carried out, to acquire knowledge, select the works that guided the discussion around the objective of the study and with that, topics such as: education in values and school curriculum were discussed. Citing authors such as: Ponce (2009), Moreira (2007), Gomes (2007), Vandal et al, (2015), Salvino et al, (2018) among others. With the current scenario of Brazilian education, it leads us to reflect on several extremely important points, which really interfere in the development of the professional, as well as in the educational development of children. Through its analysis, the article considered some of the initial challenges related to inadequate human and material resources, inconsistencies between content and pedagogical practices, and poor public participation. According to all the research carried out for the elaboration of the work, it is concluded that Brazilian education needs changes, changes that are more focused on the reality of the school.